Association between shift work and suicidal ideation: data from the Korea National Health and Nutrition Examination Survey (2008-2016) - Kyoung Kon Kim; Kyu Rae Lee; Heuy Sun Suh; Ki Dong Ko; In Cheol Hwang (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVE: Studies on the relationship between shift work and suicidal ideation are scarce. This study aimed to investigate the impact of shift work on suicidal ideation using a nationwide representative sample from the Korean working population. METHODS: The association between shift work and suicidal ideation was determined using data in 17 756 Korean workers over 19 years of age with fixed work schedules. These data were collected from the nationwide cross-sectional Korean National Health and Nutrition Examination Survey (2008-2016). The odds ratios (OR) and 95% confidence intervals (CI) for suicidal ideation were calculated by sex and age using multiple logistic regression models. RESULTS: Approximately 14% of included participants were classified as shift workers. Among male workers, evening and night shift workers had a significantly increased risk of suicidal ideation compared to day workers after adjusting for demographics, lifestyle factors, comorbidities, number of work hours, and occupational type (OR 1.89, 95% CI 1.25-2.88 for evening-fixed workers and OR 1.38, 95% CI 1.03-1.86) for night-fixed workers]. Age-stratified analyses indicated that shift workers were more likely to report suicidal ideation than day workers in young and middle-aged groups. CONCLUSION: Evening and night shift work is associated with higher suicidal ideation among male workers.